2015
DOI: 10.9734/ajaees/2015/16056
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Savings among Rural Women in Borno State, Nigeria

Abstract: The study analysed the determinants of savings among rural women in Borno State. Primary data for the study were obtained through the used of structured questionnaires from 600 respondents selected through multi-stage sampling procedure. Frequency distribution, percentages, mean, bar chart and pie chart were used to examine the socio-economic characteristics of the respondents in the study area. Logit regression model was used to determine the effects of factors (socioeconomic, institutional and cultural) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…About 47% combined different form of saving to avoid the risk of losing their hard earned money. This is in line with the finding of Adebayo (2004) and Nuhu et al (2015), who confirmed that high percentage of households belonged to at least one savings club or the other in their respective study areas.…”
Section: Savings Mobilization Strategies Adopted By Respondentssupporting
confidence: 92%
See 1 more Smart Citation
“…About 47% combined different form of saving to avoid the risk of losing their hard earned money. This is in line with the finding of Adebayo (2004) and Nuhu et al (2015), who confirmed that high percentage of households belonged to at least one savings club or the other in their respective study areas.…”
Section: Savings Mobilization Strategies Adopted By Respondentssupporting
confidence: 92%
“…The empirical studies conducted on savings mobilization in Nigeria focused more on rural households (Oluwakemi, 2013;Ekpung, Udude and Etim, 2015;Nuhu, Bzugu and Kwajaffa, 2015;Yusuf, Yusuf, Adesope and Adebayo, 2020), disregarding the urban and peri-urban households. Most of these studies focused on determinants of saving, but did not specifically estimate its effect on poverty.…”
Section: Introductionmentioning
confidence: 99%
“…But in contrast with Okeke (2007), large family size had negative consequences, because the family heads bear heavy burden which greatly undermined their investment and savings capacities. However, as against the established facts by Umar et al (2014) and Nuhu et al (2015); Figure (2b) depicts that, as the household size increases, savings rate and capacity also increases. This was because large family sizes in the study area tend to realize more outputs than those with few family members.…”
Section: Age Distribution Of Millet Farmersmentioning
confidence: 47%
“…The author found that ROSCAs makes significant difference to local communities" welfare, measured as a change in the household consumption. Nuhu et al (2015) analysed the determinants of ROSCAs among rural women in Borno State, Nigeria. The logit regression model was used to determine the effects of factors (socioeconomic, institutional and cultural) on the probability of savings of the respondents.…”
Section: Effect Of Roscas On the Performance Of Mses In Nigeriamentioning
confidence: 99%